Anthocyanins: From Mechanisms of Regulation in Plants to Health Benefits in Foods - Cappellini, Francesca; Marinelli, Alessandra; Toccaceli, Marta; Tonelli, Chiara; Petroni, Katia (Frontiers in Plant Science, 2021)
Anthocyanins represent the major red, purple and blue pigments in many flowers, fruits, vegetables and cereals. They are also recognised as important health-promoting components in the human diet with protective effects against many chronic diseases, including cardiovascular disease, obesity and cancer. Anthocyanin biosynthesis has been studied extensively and both biosynthetic and key regulatory genes have been isolated in many plant species. Here, we will provide an overview of recent progress in understanding the anthocyanin biosynthetic pathway in plants, focusing on the transcription factors controlling activation or repression of anthocyanin accumulation in cereals and fruits of different plant species, with special emphasis on the differences in molecular mechanisms between monocot and dicot plants. Recently, new insight into the transcriptional regulation of the anthocyanin biosynthesis, including positive and negative feedback control as well as epigenetic and post-translational regulation of MYB-bHLH-WD40 complexes has been gained. We will consider how knowledge of regulatory mechanisms has helped to produce anthocyanin-enriched foods through conventional breeding and metabolic engineering. Additionally, we will briefly discuss the biological activities of anthocyanins as components of the human diet and recent findings demonstrating the important health benefits of anthocyanin-rich foods against chronic diseases.